Pengaruh Bahasa Gaul pada Kalangan Remaja - Yeremias Bardi; Katharina Woli Namang; Maria Nona Yefi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This Research aims to determine the influence of the use of slang among teenagers, especially among students. Slang is a Variation of language that develops among young people and is characterized by non-standard vocabulary, often influencer by popular culture and social media. This Research uses a qualitative approach with phenomenological methods to explore subjective understanding regarding the use of slang. The Research results show that slang can influence communication, social identity and the development of the Indonesian language. The use of slang allows for more relaxed communication and strengthens social relationship among teenagers. However, excessive use can interfere with understanding formal language, potentially causing misunderstandings and reducing good language skills in formal situations. Therefore, it is important to use slang wisely according to the context and situation.